PENGARUH HAMBATAN NONTARIF DI PASAR UNI EROPA TERHADAP EKSPOR KOMODITAS CPO INDONESIA - Satria Arif Gumelar; Muhammad Irfan Affandi; Suriaty Situmorang (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This research aims to analyze which trade barriers are implemented by European Union (EU) on Indonesian Crude Palm Oil (CPO) commodity and did the non-tariff barrier named “Report on Palm Oil and Deforestation of Rainforrest” which has been ratified by the European Comission (EC) have a significant effects on Indonesian CPO export or not. This research used literature study method with secondary and primary data obtained from BPS, Indonesian National Export Development Agency, Central Bank of Indonesia, Eurostat, WTO, FAO, PASPI, Indonesian Ministry of Agriculture, Indonesian Ministry of Trade and Indonesian Palm Oil Assosiation (IPOA). The results of this research show that the EU has implemented non-tariff barriers on Indonesian CPO since 1905 with various kinds of issues such as health, social and environment. The non-tariff barrier which has been ratified in April 2017 by the European Comission did not significantly affect on Indonesian CPO export.Key words: CPO, European Union, Non-tariff Barriers.